Qaffin Secondary girls school - Eleane Jamal Jamlan; Mohammad Hasan Hijaz; Lama Hafez Aker; Sarah Wadah Zaqzouq (My University, 2015)
A school is a building which has four walls and the future inside and they are considered the most important public facilities for communities, since they are the main source for humans education, culture, and civilization. Building engineers should take comfort standards in to consideration when designing Green school in order to provide a suitable indoor climate, and protect the occupants from the effect of bad environmental surrounding and climate changes. Environmental Design is the discipline of producing the spaces of our surroundings. The comprehensive program encompasses of courses in architecture, landscape architecture, and urban design.   Our interest in this project is the implementation of environmental comfort to reach the required indoor air quality and thermal comfort, for many aspects of structural, architectural, mechanical, and electrical. To achieve this, we are going to make literature reviews, also we are going to benefit from global study cases we have reviewed in our graduation project1, and then we are going to use simulation programs in order to find the best orientation and compare the results to know which has the most impact on the energy consumption and thermal comfort to our building. We hope to produce a high performance school that would help an efficient learning, to produce the next generation who would be well aware of the concepts of green design.